15 The relationship between the buckberg index and functional capacity in stable chronic heart failure patients. (5th October 2017) - Mannion, T; Devaney, L; Fall, S; Carey, M; Jago, A; Fay, S; Pharithi, R; Egom, E; Maher, V
Abstract : Background: The Buckberg index, a diastolic to systolic pressure-time integral ratio, is a resting measure of myocardial oxygen supply and demand. It compares the delivery of oxygen to the heart muscle during diastole to the cardiac workload during systole, calculated through pulse wave analysis. A sub-optimal Buckberg index creates an imbalance which may limit cardiac performance and functional capacity in patients with chronic stable heart failure. Calculating the Buckberg Index Buckberg Index (also known as sub endocardial viability ratio or SEVR) is a pressure-time ratio calculation derived from the pressures in the aorta and left ventricle. The diastolic pressure-time integral (DPTI) indicates sub endocardial blood supply while the systolic pressure-time integral (SPTI) indicates myocardial oxygen demand. Purpose: This study was conducted to assess the association between Buckberg index and functional capacity in chronic stable HF patients. Methods: 156 clinically stable HF patients, whose weight, condition and medications had not changed in the previous 3 months participated. Buckberg Index was completed using SphygmoCor system. Systolic-to-diastolic pressure shifts were assessed by the systolic and diastolic pressure-time integrals and expressed as a percentage. Patients were then categorized as follows; Buckberg index ≤150% Buckberg index 151–200% Buckberg index ≥201% Functional capacity was evaluated via 6 Minute Walk testing, NYHA Class, 3 day accelerometer measuring daily step count (FitBit) and Kansas City Cardiomyopathy Questionnaire (KCCQ). Results: Univariate analysis (table 1) demonstrated statistically significant correlations between Buckberg index and 6 MWT distance, NYHA Class and the KCCQ, but not with daily step count (Fitbit). Although the total number of steps did not correlate with Buckberg Index, those with a BI <150% had significantly less steps (4612+/- 3114 steps/day) than those above >150% (6932+/- 4943 steps/day) p<0.01. ANOVA revealed statistically significant differences among patients grouped (1–3) by Buckberg indexes in relation to 6 MWT ((F (2, 155) = 8.737, p= 0.001)), NYHA Class ((F (2, 156) = 3.407, p= 0.036)), KCCQ Overall summary score ((F (2, 149)=7.516, p= 0.001) and KCCQ Clinical Summary Score ((F (2, 146)=11.308, p=0.001)). Conclusion: Buckberg index is associated with functional capacity in chronic stable HF patients. We recommend that HF patients are best managed if the Buckberg Index is >150%. The Buckberg Index is a very useful non invasive marker of sub endocardial viability and is associated with improved functional performance and quality of life (QOL). We observe that a Buckberg Index <150% is associated with both poor function and poor QOL.